(untitled) (Revista de Biología Marina y Oceanografía, 2022)
Peruvian moonfish Selene peruviana is an abundant resource on the Pacific coast, with a little-known biology. Regarding its parasitofauna, only two species of parasites have been registered and, given so little information, a parasitological study was carried out on 80 specimens of S. peruviana sampled from the coast of Tumbes, north of Peru, between June and October 2018. The ecological descriptors of parasitic infection/infestation, the degree of parasitic dispersal, the alpha diversity indices and the correlation the parasitological indices and biological characteristics of the fish (TL and sex) were calculated. Two species of monogeneans (Oaxacotyle oaxacensis and Metamicrocotyla macracantha), one species of trematode (Lecithocladium cristatum) and four species of copepods (Naobranchia sp., Lepeophtheirus sp., Caligus sp. and Lernanthropus sp.) were recorded. The monogenean O. oaxacensis was considered the only core species (e.g., with prevalence > 45%). The distribution found for O. oaxacensis and L. cristatum was aggregated and there was no association between TL and sex with the parasitological indices. In the case of alpha diversity indices, Margalef (Dmg), Shannon-Weaver (H´) and Pielou (J´) diversity index values were higher in females, but Simpson dominance (D) did not show differences between sexes. The diversity index of parasitic H’ showed a higher value in the sizes over sexual maturity of S. peruviana. The parasitic D index presented an opposite pattern. All the parasite species found in this study are new records for S. peruviana and for Peru.